Physiological roles for butyrylcholinesterase: A BChE-ghrelin axis. (25th November 2016) - Brimijoin, Stephen; Chen, Vicky Ping; Pang, Yuan-Ping; Geng, Liyi; Gao, Yang
Abstract: Butyrylcholinesterase (BChE) has long been regarded as an "orphan enzyme" with no specific physiological role other than to metabolize exogenous bioactive esters in the diet or in medicines. Human beings with genetic mutations that eliminate all BChE activity appear completely normal, and BChE-knockout mice have been described as "lacking a phenotype" except for faster weight gain on high-fat diets. However, our recent studies with viral gene transfer of BChE in mice reveal that BChE hydrolyzes the so-called "hunger hormone, " ghrelin, at a rate which strongly affects the circulating levels of this peptide hormone. This action has important consequences for weight gain and fat metabolism. Surprisingly, it also impacts emotional behaviors such as aggression. Overexpression of BChE leads to low ghrelin levels in the blood stream and reduces aggression and social stress in mice. Under certain circumstances these combined effects contribute to increased life-span in group-housed animals. These findings may generalize to humans, as recent clinical studies by multiple investigators indicate that, among patients with severe cardiovascular disease, longevity correlates with increasing levels of plasma BChE activity. Highlights: BChE is a hydrolase that modulates ghrelin in the blood stream. BChE alters the impact of ghrelin on its growth hormone secretagogue receptor. Manipulating the BChE-ghrelin axis may alleviate obesity, anxiety, and aggression.